2021
DOI: 10.1177/0960327121989422
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTED: ILF3-AS1 promotes cell proliferation and inhibits cell apoptosis of breast cancer by binding with miR-4429 to upregulate RAB14

Abstract: As one of the leading causes of cancer-related deaths among women, breast cancer accounts for a 30% increase of incidence worldwide since 1970s. Recently, increasing studies have revealed that the long non-coding RNA ILF3-AS1 is involved in the progression of various cancers. Nevertheless, the role of ILF3-AS1 in breast cancer remains largely unknown. In the present study, we found that ILF3-AS1 was highly expressed in breast cancer tissues and cells. ILF3-AS1 silencing inhibited breast cancer cell proliferati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 26 publications
0
1
0
Order By: Relevance
“…It has also been reported that the lncRNA ILF3-AS1 binds and inhibits miR-4429, leading to enhanced proliferation, migration, and invasion as well as impaired apoptosis in breast cancer cells (X. Zhang et al, 2021). In addition to miR-4429, the lncRNA ILF3-AS1 also sponges miR-320a, a microRNA that directly targets FOXM1 (Y.…”
mentioning
confidence: 99%
“…It has also been reported that the lncRNA ILF3-AS1 binds and inhibits miR-4429, leading to enhanced proliferation, migration, and invasion as well as impaired apoptosis in breast cancer cells (X. Zhang et al, 2021). In addition to miR-4429, the lncRNA ILF3-AS1 also sponges miR-320a, a microRNA that directly targets FOXM1 (Y.…”
mentioning
confidence: 99%